2020
DOI: 10.12688/f1000research.24654.2
|View full text |Cite
|
Sign up to set email alerts
|

Investigating a novel multiplex proteomics technology for detection of changes in serum protein concentrations that may correlate to tumor burden

Abstract: Background: To account for cancer heterogeneity, we previously introduced the concept of “personalized” tumor markers, which are biomarkers that are informative in subsets of patients or even a single patient. Recent developments in various multiplex protein technologies create excitement for the discovery of markers of tumor burden in individual patients, but the reliability of the technologies remains to be tested for this purpose. Here, we sought to explore the potential of a novel proteomics platform, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 39 publications
(50 reference statements)
0
6
0
Order By: Relevance
“…10 Our previous evaluation of QKA demonstrated lower precision and a weaker correlation between the technical duplicates (r = 0.853 to 0.862). 12 A closer look at intra-assay variation observed that 97.6% of the 1073 proteins analyzed by PEA showed a favorable coefficient of variation (CV) below 20%, 89.3% had a CV below 10%, and 0.3% showed a CV over 100% (data not shown). In contrast, 67.9% of the 1000 proteins assayed by QKA showed a CV below 20%, 47.6% had a CV below 10%, while 20.5% exhibited high variation with a CV over 100% (data not shown).…”
Section: Technical Comparison Of the Two Multiplex Proteomics Technologiesmentioning
confidence: 98%
See 2 more Smart Citations
“…10 Our previous evaluation of QKA demonstrated lower precision and a weaker correlation between the technical duplicates (r = 0.853 to 0.862). 12 A closer look at intra-assay variation observed that 97.6% of the 1073 proteins analyzed by PEA showed a favorable coefficient of variation (CV) below 20%, 89.3% had a CV below 10%, and 0.3% showed a CV over 100% (data not shown). In contrast, 67.9% of the 1000 proteins assayed by QKA showed a CV below 20%, 47.6% had a CV below 10%, while 20.5% exhibited high variation with a CV over 100% (data not shown).…”
Section: Technical Comparison Of the Two Multiplex Proteomics Technologiesmentioning
confidence: 98%
“…The workflow of the array was previously described. 12 In brief, each array included protein standards to generate a standard curve for absolute protein quantitation. The samples were analyzed in technical quadruplicates, and the technical personnel were blinded to the sample status.…”
Section: Quantibody ® Human Kiloplex Arraymentioning
confidence: 99%
See 1 more Smart Citation
“…The micro-ELISA array technology from RayBiotech combines 25 nonoverlapping glass-slide arrays to perform up to 1000 miniature sandwich ELISAs simultaneously, targeting mostly inflammation-related proteins, including cytokines, chemokines, growth factors, tumor markers, and transcription factors ( 37 , 38 , 39 , 40 , 41 , 42 , 43 ). Each 75 mm × 25 mm glass slide contains 16 identical antibody subarrays, where each subarray multiplexes 40 different proteins arranged in technical quadruplicates.…”
Section: Planar Immunoassaysmentioning
confidence: 99%
“…However, Ren et al. ( 41 ) reported incongruities between the micro-ELISA array and ELISA data for nine protein candidates in pancreatic cancer. The overall findings illustrated that inconsistencies in protein quantification between different ultrasensitive multiplex immunoassays are highly analyte-dependent.…”
Section: Limitations and Technical Comparisonsmentioning
confidence: 99%